2023
DOI: 10.1111/faf.12754
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variability in the fish assemblage around Japan over the last century and early warning signals of regime shifts

Abstract: Physical processes such as climatic and oceanographic variability, particularly decadal variability or climatic regime shifts defined as dramatic, abrupt changes in conditions that are persistent in time (Conversi et al., 2015), such as indicated by the Pacific Decadal Oscillation (PDO) and the El Niño-Southern Oscillation (ENSO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 105 publications
(242 reference statements)
0
1
0
Order By: Relevance
“…This change impedes nutrient exchange between the upper and subsurface layers and reduces primary production in the upper layer, impacting the entire marine ecosystem (Li et al, 2020). In addition, the marine ecosystems in Japanese waters were strongly influenced by a typical wasp-waist control (Tian et al, 2023), in which a single species, or at most several species, of small planktivorous fishes entirely dominate marine ecosystems. Skud (1982) and Cury et al (2000) suggested that dominant small pelagic fish respond to environmental factors, and subordinate species, in turn, respond to the abundance of the dominant species, particularly through competition for prey.…”
mentioning
confidence: 99%
“…This change impedes nutrient exchange between the upper and subsurface layers and reduces primary production in the upper layer, impacting the entire marine ecosystem (Li et al, 2020). In addition, the marine ecosystems in Japanese waters were strongly influenced by a typical wasp-waist control (Tian et al, 2023), in which a single species, or at most several species, of small planktivorous fishes entirely dominate marine ecosystems. Skud (1982) and Cury et al (2000) suggested that dominant small pelagic fish respond to environmental factors, and subordinate species, in turn, respond to the abundance of the dominant species, particularly through competition for prey.…”
mentioning
confidence: 99%